2006
DOI: 10.4049/jimmunol.177.2.983
|View full text |Cite
|
Sign up to set email alerts
|

Role of Immunoproteasomes in Cross-Presentation

Abstract: The evidence that proteasomes are involved in the processing of cross-presented proteins is indirect and based on the in vitro use of proteasome inhibitors. It remains, therefore, unclear whether cross-presentation of MHC class I peptide epitopes can occur entirely within phagolysosomes or whether it requires proteasome degradation. To address this question, we studied in vivo cross-presentation of an immunoproteasome-dependent epitope. First, we demonstrated that generation of the immunodominant HY Uty246–254… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
63
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 50 publications
3
63
1
1
Order By: Relevance
“…Immunoproteasomes, which have been implicated in cross-presentation [23], could also account for GP276 poor cross-presentation since it can downregulate GP276 presentation [24]. We have detected LMP7 expression in DC2.4 (unpublished data), which concurs with the previous data showing that immunoproteasomes are expressed in DC irrespective of their maturation states [25].…”
Section: Discussionsupporting
confidence: 91%
“…Immunoproteasomes, which have been implicated in cross-presentation [23], could also account for GP276 poor cross-presentation since it can downregulate GP276 presentation [24]. We have detected LMP7 expression in DC2.4 (unpublished data), which concurs with the previous data showing that immunoproteasomes are expressed in DC irrespective of their maturation states [25].…”
Section: Discussionsupporting
confidence: 91%
“…When we analyzed the presentation of the endogenously expressed male minor Ag UTY on mouse splenocytes, we observed that the epitope is not only LMP7 dependent, as previously reported (14,33), but also dependent on LMP2 (Figs. 1A, 2E).…”
Section: Discussionsupporting
confidence: 74%
“…The HY-Ag-derived MHC-I epitope UTY 246-254 is LMP7 and LMP2 dependent Generation of the CTL epitope UTY 246-254 (ubiquitously transcribed tetratricopeptide repeat gene, Y-linked), derived from the endogenously expressed Y-chromosome-encoded HY-Ag, has been demonstrated to be LMP7 dependent (14,33). To confirm this result and to investigate whether the other immunoproteasome subunits LMP2 and MECL-1 were similarly affecting this epitope, UTY 246-254 presentation on the H-2D b class I molecule of malederived splenocytes was determined with a UTY 246-254 -specific T cell hybridoma in lacZ assays (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1 d and e). A major conclusion from our work is that only a subset of CD8 ϩ DCs possesses a highly efficient mechanism for endosome-to-cytosol transport [where access to the TAP/proteasome pathway is gained (5)] that makes it particularly specialized at cross-presentation of exogenous Ag.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence to suggest that the specialized ability of DCs for cross-presentation may be explained in part by the presence of a unique, size-selective intracellular pathway for export of Ag from endosomal compartments into the cytosol for access to the conventional MHC class I processing pathway (2), although this has not specifically been shown for the CD8 ϩ DC subset. Recent data also suggest that the cytosolic crosspresentation pathway is the major relevant mechanism in vivo (5) and that the machinery that confers cross-presentation specialization is located downstream from Ag uptake (6). Despite the progress in our understanding of the mechanisms of crosspresentation, in vivo application of cross-presentation to manipulate (enhance or reduce) a CD8 ϩ T cell response remains to be exploited.…”
mentioning
confidence: 99%